MVR ABBAS: MULTIMEDIA VIRTUAL REALITY GAME BERBICARA BAHASA ARAB UNTUK SISWA JENJANG MENENGAH PERTAMA - Novita Kusumadewi; Aziz Fajar Nurizki; Andri Bekti Pratama; Zukhaira Zukhaira (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
Language learning must be carried out hierarchically from listening skills to writing skills. Although learning Arabic in Indonesia has been going on for centuries, learning listening skills and speaking Arabic still lacks adequate attention and focus. This happens because there is no proper language learning media available. Teachers rarely use and even never use media in learning Arabic, especially speaking skills. Based on the above problems, a solution is needed in the form of a variety of learning media that can be used by teachers and students in speaking learning, namely MVR Abbas (Multimedia Virtual Reality Arabic Speaking Game), an Arabic Speaking Game which not only teaches and trains related speaking skills only, but also has the contents of the material based on intercultural education considering learning languages will not be separated from learning the culture of the language.